(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Cervical cancer remains a significant public health concern in Indonesia, with HPV infection as the primary etiological factor. Despite the availability of HPV vaccination as a crucial preventive measure, awareness and uptake remain suboptimal, particularly among elementary school-aged children and their parents. This community service program aimed to enhance HPV vaccination knowledge and acceptance through comprehensive educational interventions targeting elementary school students and their parents/guardians in Ciangsana and Nagrak Villages, Bogor, Indonesia. The program was conducted through a structured educational intervention involving 28 elementary school students (median age 10 years) and 25 parents/guardians (median age 35 years). Activities included interactive educational sessions, pre-post knowledge assessment, and collaboration with local health centers. The educational program successfully improved HPV vaccination knowledge among parents/guardians (mean score increase from 4.440 to 4.880, p=0.046). While students showed increased engagement and modest improvement (mean score from 5.107 to 5.357), their knowledge enhancement was not statistically significant (p>0.244). The program established effective partnerships between the medical faculty, local health centers, and community residents. Educational materials developed showed good reliability (Cronbach’s alpha 0.661 for parents and 0.709 for students). This community service program demonstrated the effectiveness of targeted educational interventions in promoting HPV vaccination awareness, particularly among parents, while highlighting the need for age-appropriate educational strategies and sustainable community partnerships for health promotion initiatives. — Kanker serviks masih menjadi masalah kesehatan masyarakat yang signifikan di Indonesia, dengan infeksi HPV sebagai faktor penyebab utama. Meskipun vaksinasi HPV tersedia sebagai langkah pencegahan penting, kesadaran dan cakupannya masih rendah, terutama di kalangan anak usia sekolah dasar dan orang tua mereka. Program pengabdian masyarakat ini bertujuan meningkatkan pengetahuan dan penerimaan vaksinasi HPV melalui intervensi edukasi komprehensif yang ditargetkan kepada siswa sekolah dasar dan orang tua/wali di Desa Ciangsana dan Nagrak, Bogor, Indonesia. Program dilaksanakan melalui intervensi edukasi terstruktur yang melibatkan 28 siswa sekolah dasar (median usia 10 tahun) dan 25 orang tua/wali (median usia 35 tahun). Kegiatan mencakup sesi edukasi interaktif, penilaian pengetahuan pre-post, dan kolaborasi dengan puskesmas setempat. Program edukasi berhasil meningkatkan pengetahuan tentang vaksinasi HPV pada kelompok orang tua/wali (peningkatan skor rata-rata dari 4,440 menjadi 4,880, p=0,046). Meskipun siswa menunjukkan peningkatan partisipasi dan perbaikan moderat (skor rata-rata dari 5,107 menjadi 5,357), peningkatan pengetahuan mereka tidak signifikan secara statistik (p>0,244). Program ini berhasil membangun kemitraan efektif antara fakultas kedokteran, puskesmas, dan warga masyarakat. Materi edukasi yang dikembangkan menunjukkan reliabilitas yang baik (alpha Cronbach 0,661 untuk orang tua dan 0,709 untuk siswa). Program pengabdian masyarakat ini menunjukkan efektivitas intervensi edukasi yang ditargetkan dalam meningkatkan kesadaran vaksinasi HPV, khususnya di kalangan orang tua, sambil menegaskan pentingnya strategi edukasi yang sesuai usia dan kemitraan berkelanjutan dengan masyarakat dalam inisiatif promosi kesehatan.